The Role of Prehabilitation on Functional Outcomes After Radical Prostatectomy: A Scoping Review - Bilyk, Andrii; Bruska, Natalia; Kołodziej, Przemysław; Hebda, Patryk; Cemaga, Roman; Patalong, Mikołaj Franciszek; Szplit, Ewa; Czapliński, Mieszko; Michnowska, Wiktoria; Pustuła, Paweł (Quality in Sport, 2026)
Background Radical prostatectomy is a primary treatment for localized prostate cancer but often results in urinary incontinence and erectile dysfunction, significantly impacting patient quality of life. Prehabilitation, defined as the optimization of physical capacity before surgery—aims to increase physiological reserve to buffer the functional decline caused by surgical trauma. Aim The primary objective of this scoping review is to comprehensively evaluate the efficacy of various prehabilitation modalities on functional outcomes following radical prostatectomy. Specifically, this report assesses the impact of preoperative Pelvic Floor Muscle Training, High-Intensity Interval Training, resistance exercise, and multimodal lifestyle interventions on the recovery of urinary continence, erectile function, and cardiorespiratory fitness. Material and Methods A review of RCTs, prospective cohorts, and meta-analyses published through 2025 was conducted. The synthesis included diverse interventions and measured outcomes using validated tools like the EPIC and IIEF scales, as well as objective pad tests. Results Preoperative PFMT with biofeedback significantly speeds early urinary recovery. However, long-term results match standard postoperative care, indicating a "bolus effect" that accelerates initial progress without altering the final anatomical plateau. Systemic prehabilitation via HIIT and resistance training was found to significantly improve cardiorespiratory fitness and muscular strength, leading to a substantial reduction in post-operative complications, though the direct translation to urological function remains heterogeneous. Conclusions Prehabilitation is a safe and effective strategy to enhance early functional recovery. While it cannot fully overcome severe anatomical deficits, it provides a crucial buffer that speeds the return to continence. Evidence strongly supports integrating multimodal prehabilitation into standard urological care.